Growth, condition, survival and feeding rate of the Pacific oyster (Crassostrea gigas Thunberg) cultured in three distinct South African environments - Pieterse, Aldi (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.